Effect of pharmacist-led intervention on progression of diabetic complications at two tertiary care hospitals of Malaysia - Muhammad Zahid Iqbal; Amer Hayat Khan; Syed Azhar Syed Sulaiman; Aznita Ibrahim; Nor Shaffinaz Binti Yusoff Azmi; Muhammad Shahid Iqbal; Fahad I Al-Saikhan; Salah-; Eldowaik Mohamed Salah Saad (Wolters Kluwer Medknow Publications, 2021)
Background and Objective: Diabetes mellitus is a chronic disease which can lead to different complications in patients if not treated properly. An appropriate intervention from health care providers is needed to stop and decrease the progression of diabetic complication in diabetic patients. This study aimed to measure the effect of pharmacist intervention on improvement in sign and symptoms and progression of diabetic complications in diabetic patients. Methodology: Diabetic patients were randomly selected and divided into two groups from two tertiary care hospitals. Control group contained those 200 patients who were receiving usual treatment from hospitals. In contrast, the intervention group included those 200 patients who were receiving conventional treatment from hospitals together with separate counselling sessions with pharmacists from Diabetes Medication Therapy Adherence Clinic departments. The study continued for 1 year and two follow-up visits for both groups. A prevalidated data collection form was used to measure the improvement in sign and symptoms and progression of diabetic complication in diabetic patients. Statistical Package for the Social Sciences (SPSS) version 24 was used to analyze the data. Results: The average hemoglobin A1c (HbA1c) values decreased up to 1.43% in the control group and 2.82% in the intervention group. The intervention group showed significant improvement in HbA1c between groups (P < 0.05). The results of univariate and multivariate regression analysis showed that a statistically significant (P < 0.001) improvement was observed in all the predictors of diabetic complications among in the intervention group when compared with the control group. Conclusion: Statistically significant reduction in the sign and symptoms of diabetic complications was observed in the intervention group at the end of 1 year. The progression of diabetic neuropathy was significantly reduced in the pharmacist intervention group.